Education other: teaching actions as decolonial and intercultural pedagogy - Costa da Silva, Roberto Carlos (2018)
The objective of this communication is to present experiences of pedagogical decolonies developed in schools of the state public network (RJ / São Gonçalo and Duque de Caxias), with new knowledge based on curricular “transgressions” and establishing new pedagogical possibilities in a perspective of intercultural education. These activities were marked out in Law 10.639 / 03, which determines the teaching of African History and Afro-Brazilian Culture in school space, as points of a Thought-Other for an anti-racist struggle and the dismantling of a perspective European hegemony in the curricula of school subjects.